Nekaj podatkov iz Besedotvornega slovarja slovenskega jezika za črko B po SSKJ - Stramljič Breznik, Irena (Jezik in slovstvo, 2002)
A dictionary of word families is primarily useful for the linguistic science, providing: (a) an exact picture of the ratio of non-derived and derived words; (b) information on the average size of word families, including the extreme upper and lower ends of the scale; (c) a list of all possible word-formation suffixes and their frequencies. Such a dictionary may be expanded by adding meanings of derived and compound words and their use in discourse, thus making it very similar in terms od its usefulness to the monolingual national dictionary, except that the alphabetical system of organisation is replaced by the word-family one. It could also serve as a source for the production of a students' word-information dictionary, which would selectively reduce the word families depending on the frequency of derived and compound words as verified in a text corpus. Corpus analysis could also be used to determine the most common structure of word families by individual parts of speech. This data could then be used to produce a dictionary for non-native users which would provide an insight into the most typical patterns of formation of new words and help the users to acquire und undestand new words on the basis of analogy. An alternative might be to organise such a dictionary on the principle of semantic fields, as it is highly probable that words belonging to a semantic field determined by a common hypernym also have a very similar structure of their word families. Such a dictionary would provide learners of Slovene with several kinds of data at the same time, a possibility to compare the conceptual, word-family and semantic structure of their mother tongue and Slovene
Keywords: Slovene; slovenščina; word formation; besedotvorje; slovarji; Besedotvorni slovar slovenskega jezika